Assessment of Achievement Motivation, Personality, and their relationship with Socio-Economic Class of the Engineering students - R. S. Pathania (Universitas Pendidikan Indonesia (UPI), 2023)
The study examined the relationships between engineering students' personalities, socioeconomic status, and drive for achievement. Six hundred engineers were chosen at random from the engineering institutes at Punjab Technical University. The primary goals of the study were to examine the associations between engineering students' socioeconomic level and their motivation for academic accomplishment as well as the associations between their personalities and their socioeconomic status. The results showed no significant difference in the relationship between achievement motivation and socioeconomic status of engineering students, and it was also found that there was no significant difference between the personality and socioeconomic status of engineering students. At the threshold, the significant connection was determined.